Traumatic Symmetric Biparietal Extradural Hematoma: Report of Two Cases - G. Lakshmi Prasad; Sumit Sinha (Indian Journal of Neurosurgery, 2017)
Traumatic bilateral epidural hematomas (EDHs) are uncommon and are mostly found in the frontal region because of extension of fracture across the midline and tear of venous sinus. Authors report two cases of mirror image biparietal extradural hematoma after sustaining a high-velocity motor vehicle accident. Both were adult males and had a very low admission GCS of less than 8. Emergency hematoma evacuation was performed bilaterally and good outcomes were achieved in both. Mean follow-up duration was 9 months. The pathophysiologic mechanisms are different from solitary EDH as are the clinical features and outcomes. The rarity of these lesions and surgical nuances are highlighted.